A Case Report on Acute Hypersensitivity Reaction to Metronidazole Injection in a Female patient - G, Nandaperumal.; .D, Bhuvaneshwari; Angel.S, Jacintha Abisha; Dheenadhayalan, M.; Sundaram, P. Shanmuga; Karthickeyan, K.; Sri, M.K. Sundar (Journal of Neonatal Surgery, 2025)
This case report discusses a 75-year-old female patient with a history of varicose veins, hypertension, and stroke, who presented with pain, swelling, and discharge from the left leg, ultimately diagnosed with bilateral lower limb lymphedema and lymphangitis. The patient experienced an acute hypersensitivity reaction after the administration of intravenous metronidazole, characterized by facial urticaria. The mechanism of this Type I hypersensitivity reaction involves sensitization to metronidazole, leading to IgE-mediated mast cell degranulation upon re-exposure. Given the patient's allergic reaction, clindamycin was identified as a safe alternative antibiotic, effective against anaerobic infections and Gram-positive cocci. This case underscores the importance of vigilance for drug-induced hypersensitivity reactions, particularly in older patients with multiple comorbidities, and highlights the necessity for careful monitoring and personalized antibiotic therapy to ensure patient safety.